Estimasi Data Insight Social Media Ads Menggunakan Neural Network, Linear Regression dan Deep Learning - Zurni Laila; Nuri Cahyono (Jurnal Sistem Komputer dan Informatika (JSON), 2023)
PT IlmuKomputerCom Braindevs is a professional training company that sells products in the form of training services (courses). In service companies such as PT IlmuKomputerCom Braindevs Sistema, holding courses with high demand is the key to increasing company profits. The marketing division is a very important division in the context of holding a course/training. To manage the target participants needed in organizing training. In addition, PT IlmuKomputerCom Braindevs also needs to estimate advertising costs and ad duration in the training promotions that will be held. To analyze the marketing division using data mining techniques and the Cross-industry standard process for data mining (CRISP-DM) method to obtain the desired estimate. So to get the final result of the participant's estimated value, ad duration and ad cost, an algorithm that has the most accurate accuracy is needed according to the reference from the results of the comparison of algorithms by looking at the value of RMSE (Root Mean Square Error). The closer the resulting value is to 0, the better the estimated accuracy of the RMSE (Root Mean Square Error) estimate will be.